2020
DOI: 10.21203/rs.3.rs-25034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-destructive collection survey of the historical Classense Library. Part II: Conservation scenarios

Abstract: To enable the development of conservation strategies for valuable historical collections, an innovative non-destructive and non-invasive survey was conducted at an historical library (Classense Library, Ravenna, Italy) to assess how management scenarios may influence the future conservation state of the collections. For the first time, the results in terms of acidity and degree of polymerisation of book collections were elaborated using the Collection Demography dose-response function modelled for historic pap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…As the collections were separated into climate-controlled and non-controlled collections by the library only six years ago, they have been grouped together for parts of this study, as the last six years of degradation represent an insignificant period compared to the age of the objects. The collections will be separately dealt with in Part II [31] as the effects of the different environments on the future condition of books will be modelled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the collections were separated into climate-controlled and non-controlled collections by the library only six years ago, they have been grouped together for parts of this study, as the last six years of degradation represent an insignificant period compared to the age of the objects. The collections will be separately dealt with in Part II [31] as the effects of the different environments on the future condition of books will be modelled.…”
Section: Resultsmentioning
confidence: 99%
“…Visual assessment was used as it has been demonstrated that physical deterioration such as missing pieces influence readers/visitors' subjective judgments of fitness-for-use to a greater extent than discolouration or tears, which have little or no influence [30]. In Part II [31], the results will be further elaborated with the support of a dose-response function recently modelled for historical paper [32], in order to assess potential preservation scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…A good example of nondestructive research was provided by a group of researchers who studied a historical library collection in Ravenna, Italy, to assess the extent of the collection's deterioration and to obtain a characterization of the paper. This study also included a calculation ofto the collection lifetime which was done by combining the findings of chemical properties with environmental conditions using the dose-response function [22,23]. Strlič et al established a database of the mechanical and chemical properties of paper which describes the interdependence of composition and degradation, and which in turn may have an impact on conservation research and practice [24].…”
Section: Introductionmentioning
confidence: 99%